The Process of Translation and Cross‐Cultural Adaptation of Functional Assessment Tools for Dementia: A Systematized Review - Freddie O'Donald; Clara Calia (Health Science Reports)
Abstract Background and Aims A decline in function related to impairment in cognitive abilities is required for diagnosing dementia. Cultural diversity influences everyday functioning, suggesting that functional assessment tools need to be culturally dependent. Therefore, this systematized review aimed to explore the translation and cross‐cultural adaptation of functional assessment tools designed to support dementia diagnosis. Methods A systematic search of five electronic databases (CINAHL Plus, EMBASE, PubMed/MEDLINE, PsycINFO) was conducted from inception until September 2023. Quality assessment criteria were then utilized to evaluate the process of cross‐cultural adaptation and psychometric properties of identified functional assessment tools. Results Fifteen studies relating to adapted functional assessment tools in 11 languages were identified. It was found that less than half of these studies fully adhered to established guidelines for the translation and cross‐cultural adaptation of instruments. Regarding psychometric properties, while the internal consistency and reliability of included measures were generally strong, there was variability in evaluating other psychometric properties, notably structural validity, measurement error, and cross‐cultural validity. Conclusions This review underscores the need for researchers and clinicians to follow standardized guidelines for translating and cross‐culturally adapting functional assessment tools for dementia and ensuring the comprehensive evaluation of psychometric properties in cross‐cultural settings. Researchers and clinicians should consider whether the psychometric properties and characteristics of an adapted functional activity measure are suitable for use in their population of interest.